Division of Precipitation Stage Based on Optimal Dissection Method:A Case Study in Hefei Station - HUANG Bingjie; ZHOU Yuliang; JIN Juliang; ZHOU Ping; SHEN Jie; NING Shaowei (Renmin Zhujiang)
Based on daily precipitation data of Hefei station from 1953 to 2019,this paper divides stages of precipitation in Hefei preliminarily by the optimal dissection method,and identifies the precipitation stages ultimately according to the general atmospheric circulation of precipitation stages.The results show that six stages can be identified in Hefei,including the stage of dry season in winter (November 29 to February 12 next year),the stage of rainy season in early spring (February 13 to April 4),the stage of rainy season in spring and early summer (April 5 to June 19),the stage of plum rainy season (June 20 to July 12),the stage of rainy season in midsummer (July 13 to September 4) and the stage of rainy season in autumn (September 5 to November 28).The plum rainy season and the rainy season in midsummer are the two main rainy seasons,of which the average daily precipitation is 6.9 mm and 4.3 mm respectively,and the corresponding atmospheric circulation is predominant and flourishing periods of summer monsoon respectively;the stage of dry season in winter and the stage of rainy season in autumn are periods with rare precipitation,of which average daily precipitation is 1.1 mm and 2.0 mm respectively,and the corresponding atmospheric circulation is flourishing periods of winter monsoon and transition period of summer to winter monsoon respectively;and the remaining two periods are the stage of rainy season in early spring and the stage of rainy season in spring &early summer,of which the average daily precipitation is 2.3 mm and 3.2 mm respectively,and the corresponding atmospheric circulation is transition period of winter to summer monsoon and initial period of summer monsoon respectively.Precipitation in Hefei is strongly affected by the monsoon,and the atmospheric circulation of each stage is relatively stable.